Model of administrative and legal regulation and the water and sewage sector - Walczak-Kowalik, Beata (Studia Iuridica Toruniensia, 2021)
The article is devoted to the analysis of the specific role played by the organs of the Polish Water Economy in the water and sewage services sector, in particular to the possible assignment to these bodies of the functions of the regulator of the sector.